Mutation derivation in shaping linguistic picture of the world (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The proposed exploration introduces us to derive from the names of body parts that form the Ukrainian language picture of the world through the prism of mutation derivation. In the language world of the Ukrainian people represented by these estimates, which are based on similarity lokatyvnist, procedural, size, functionality. Most nouns witnessed a seventh «place».
Keywords: linguistic picture of the world; evaluation-cognitive; names of body parts